IN VITRO REGENERATION OF PLANTLETS FROM NODAL EXPLANTS OF NYCTANTHES ARBOR-TRISTIS LINN. AND EVALUATION OF GENETIC FIDELITY THROUGH RAPD ANALYSIS - R. C. SAHU; A. SAHU; S. PADHI; L. PATTANAIK; R. R. MISHRA; J. PANIGRAHI (The Bioscan, 2012)
Plantlet regeneration in Nyctanthes arbor-tristis (Family: Oleaceae), a medicinal shrub, from nodal and shoot tip explants on basal MS medium was studied. Maximum number of adventitious shoots were differentiated from nodal explants on MS medium supplemented with 8μM BA (6.2±0.83). The MS medium fortified with 8μM BA and 2μM NAA induced callus mediated organogenesis, and highest multiple shoot proliferation (10.4±0.89) from the nodal explants. MS medium with 6μM BA and 3μM NAA showed maximum (5.54±0.32cm) elongation of shoots. The elongated shoots, incubated overnight on one fourth MS medium with IBA (2.0μM), were successfully rooted on plant growth regulator free one fourth strength liquid MS medium. Regenerated plantlets were successfully established in soil where 80±2% of them survived into morphologically normal and fertile plants. Nine responded RAPD primers were used to assess genetic fidelity of regenerated plantlets along with the donor plant. These nine primers generated 24 amplified products (275 to 1150bp), and the homogenous amplification pattern confirmed the genetic uniformity of the in vitro regenerated plantlets and substantiated the efficacy of this protocol for in vitro propagation of N. arbor-tristis, to meet the demand of herbal industry.